Implementation of Islamic Education and Wasathiyah Da'wah for Millennial Generation with Al-Qur'an Perspective in Facing Society 5.0 - Wulandari, Widya (Jurnal Pendidikan Agama Islam, 2022)
Purpose – The purpose of this study was to determine the implementation of Wasathiyah education and da'wah for the millennial generation from the perspective of the Koran in facing society 5.0. The challenges and obstacles will be more complex. Methods -- The research method used was literature research. The data collection technique was documentation. The data were analyzed by using critically performed text analysis. Design/methods/approach – The research method used was literature research. The data collection technique was documentation. The data were analyzed by using critically performed text analysis. Findings – The results showed that Islamic education for the millennial generation is facing increasingly rapid technological developments. They are not affected by extreme groups in the name of Islam, and it is not easy to declare heresy against someone who has a different opinion. A preacher must be creative, and innovative to adapt with the developments of technology so that the millennial generation is interested in Islamic teaching. Research limitations – This study has limitations on the observed cases regarding the implementation of Islamic education and wasathiyah da'wah for the millennial generation. Originality/value– The research findings provide an overview of the deflection of the understanding of the wasathiyah concept regarding trust education for the millennial generation. Islamic education that is not delivered properly may cause radical actions. Technology makes da’wah reach all circles. In the midst of the globalization revolution, it becomes an opportunity for preachers (da'i) to be more creative and innovative in conveying messages. In other words, da’wah activities should be improved, both in terms of supplies and facilities (tools/materials).